NEOPROTEROZOIC FLOOD BASALTS OF THE UPPER BEDS OF THE VOLHYNIAN SERIES (EAST EUROPEAN CRATON) - Białowolska A.; Bakun-Czubarow N.; Fedoryshyn Y. (My University, 2002)
The effusive rocks of the Ratno Beds of the Volhynian Series known from the western slope of the Ukrainian Shield are represented by lower Vendian flood basalts whose normative composition is that of quartz tholeiites. These are plagioclase-pyroxene basalts displaying intergranular, intersertal, doleritic, ophitic and amygdaloidal textures; they range from aphanitic to medium-grained and contain about 7 vol. % of palagonite - an altered glass with a high iron and considerable magnesium content. The range in composition of plagioclases (andesine-bytownite) and clinopyroxenes (augite-ferropigeonite) suggests that the Ratno Beds basalts formed by fractional crystallisation of a parent magma. Residual magma underwent liquation, producing a separate acid glass (69-73 wt. % of SiO2) phase within a basic one considerably poorer in SiO2 but rich in iron and magnesium. The Ratno Beds basalts are relatively rich in silica, iron, titanium and vanadium as well as in REE and LREE in particular but poor in Ni, Co and Cr. Normative composition, geochemical characteristics and tectonic position suggest classification as continental quartz tholeiites. Hydrothermal solutions are responsible for rich native copper mineralisation in basalts of certain parts of Volhynia (Ivance and Policy). The Vendian volcanism of the Volhynian Series lithologically correlated with the Sławatycze Series of eastern Poland, can be related to continental rifting accompanying the breakup of Rodinia, with crustal fractures mainly running concordantly with the suture zone between Fennoscandia and Sarmatia, thus almost perpendicular to the Tornquist rift; other fracture trends may also have controlled Vendian volcanism.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская